Introduction to ISTAC's Malay World's Programme - Zakariya, Hafiz (2018)
The rebranded ISTAC was launched in October 2017. Its objective is to proliferate studies on Islamic Civilization and the Malay World. One integral component of postgraduate study at ISTAC is the Malay World studies. This presentation explains the major concepts and structure of the Malay World Studies at ISTAC.